Maqasid Al-Syariah Sebagai Landasan Etika Ekonomi Politik Islam Di Indonesia - Abdalul Zikri; Kurniati Kurniati; A Qadir Gassing (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The study purpose was to examine maqāṣid al-syarī‘ah as an ethical foundation in Islamic political economy and to analyze its implementation in Indonesia through zakat as a strategic policy instrument. The study emphasizes that Islamic political economy cannot be separated from ethical dimensions and sharia objectives, while highlighting the contemporary tendency to limit Islamic economics to micro aspects and neglect its broader political-economic role in regulating welfare distribution and social justice. Materials and methods. This study employed a library research method with a normative–conceptual approach. The analysis was conducted through classical and contemporary Islamic economic literature, zakat regulations in Indonesia, and the perspectives of scholars and academics. Data were examined qualitatively to identify the normative foundations of maqāṣid al-syarī‘ah and their relevance to economic and political policy frameworks. Results. The findings indicate that maqāṣid al-syarī‘ah positions public welfare as the primary orientation of economic and political policies, manifested through principles of justice, equity, sustainability, and protection of fundamental human rights. In the Indonesian context, zakat functions as a strategic instrument of redistribution, poverty alleviation, community empowerment, and sustainable economic development. However, zakat management still faces challenges related to collection optimization, supervision, and institutional transparency. Conclusions. Strengthening regulatory frameworks and governance of zakat institutions is urgently needed to ensure effective implementation of maqāṣid al-syarī‘ah within Indonesia’s Islamic political economy system. Enhanced accountability, coordination, and policy integration are essential to maximize zakat’s role in achieving social justice and sustainable welfare.